Classifications of countries based on their standard of living - Ahmad, Zahoor; Nisar, Lubaina (Pakistan journal of commerce and social sciences, 2014)
In the body of the literature, it is celebrated that human well-being becomes the key subject in measuring the economic development. The purpose of this study is to classify the countries with respect to their standard of living on the basis of economic growth, health, education and quality of environment by using cluster analysis and self-organizing feature map. The data have been obtained from the World Bank Report 2011, United Nation Development Program and the United Nation Statistics Division. The results of this study reveal that health and quality of environment indicators playing most important role for classification of the countries.